Inheritance Rights of Children Born Outside Marriage in Mixed Marriages: Normative Conflicts and Harmonization under Indonesian Law - Titik Triwulan Tutik; Nur Syam; Tri Hidayati; Agus Aditoni; Mahtumridho Ghufron bin Simun (El-Mashlahah, 2026)
Indonesia’s pluralistic legal system generates persistent uncertainty on the inheritance rights of children born out of wedlock (marriage), particularly in mixed marriages where Islamic law, civil law, and nationality law intersect. Normative inconsistencies among these legal regimes create disputes concerning filiation, child recognition, and inheritance entitlement. The particular study examined the inheritance rights of extramarital children (also known as children born out of wedlock) in mixed marriages by analyzing the interaction between Indonesian legal norms, the implications of Constitutional Court Decision No. 46/PUU-VIII/2010, and comparative developments in selected Muslim-majority jurisdictions. Employing a normative juridical approach, the study combined statutory, conceptual, comparative, and maqāṣid al-syarī‘ah analyses of legal systems in Malaysia, Morocco, Tunisia, Turkey, Pakistan, Bangladesh, Jordan, and Egypt. The findings found out a fundamental conflict between the Civil Code and the Compilation of Islamic Law (KHI). While the Civil Code recognizes inheritance rights arising from paternal acknowledgment, KHI limits lineage and inheritance to the maternal line. Although Constitutional Court Decision No. 46/PUU-VIII/2010 expanded civil relations between extramarital children and their biological fathers through scientific evidence, the absence of implementing regulations has produced inconsistent judicial interpretations. Comparative analysis demonstrated a growing tendency among Muslim-majority countries to strengthen child protection through maqāṣid-based legal reforms. In Indonesia, the expansion of mandatory bequests (wasiat wajibah) offers a practical mechanism for achieving inheritance justice without altering Islamic lineage doctrine. Legal harmonization, therefore, requires comprehensive regulation that prioritizes the best interests and welfare of the child while maintaining coherence between Islamic and constitutional principles.